Rapid establishment of a COVID‐19 convalescent plasma program in a regional health care delivery network. Issue 10 (21st August 2020) - Blackall, Douglas; Wulff, Shephali; Roettger, Timothy; Jacobs, Lauren; Lacasse, Alexandre; Patri, Manokiran; Zinser, Phillip; Pherez, Francisco; Jamkhana, Zafar; Frey, Sharon E.; Smith, Linda; Goel, Ruchika; et al.
Abstract: Background: COVID‐19 convalescent plasma (CCP) represents an appealing approach to the treatment of patients with infections due to SARS‐CoV‐2. We endeavored to quickly establish a sustainable CCP transfusion program for a regional network of health care facilities. Study design and methods: A regional collaborative group was activated to address the issues necessary to implementing a CCP transfusion program and making the program sustainable. A wide range of health care providers including physicians (critical care, infectious disease, transfusion medicine), nurses, pharmacists, laboratorians, and information technology (IT) specialists were required to make the program a success. Results: The CCP implementation team initially consisted of four members but quickly grew to a group of nearly 20 participants based on different issues related to program implementation. Overall, six major implementation "themes" were addressed: (a) registration of individual hospitals and principal investigators with a national investigational new drug research protocol; (b) collaboration with a regional blood donor center; (c) targeted recruitment of convalesced donors; (d) IT issues related to all aspects of CCP ordering, distribution, and transfusion; (e) prioritization of patients to receive CCP; and (f) evaluation of CCP products including antibody characteristics and patient response to therapy. Conclusion: Within 4 weeks of initiation, CCP was successfully transfused at multiple hospitals in our regional health care delivery system. A program infrastructure was established that will make this program sustainable into the future. This approach has broader implications for the success of multi‐institutional programs requiring rapid implementation.